2021
DOI: 10.3390/ijerph182413339
|View full text |Cite
|
Sign up to set email alerts
|

Climate Solutions Double as Health Interventions

Abstract: The climate crisis threatens to exacerbate numerous climate-sensitive health risks, including heatwave mortality, malnutrition from reduced crop yields, water- and vector-borne infectious diseases, and respiratory illness from smog, ozone, allergenic pollen, and wildfires. Recent reports from the Intergovernmental Panel on Climate Change stress the urgent need for action to mitigate climate change, underscoring the need for more scientific assessment of the benefits of climate action for health and wellbeing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…Simultaneously, it is also proven that voluntary family planning can influence and benefit climate change, mostly through slowing future population growth, especially in low- and middle-income countries [ 47 ]; thus, the connection between birth rate and climate change is indisputable.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, it is also proven that voluntary family planning can influence and benefit climate change, mostly through slowing future population growth, especially in low- and middle-income countries [ 47 ]; thus, the connection between birth rate and climate change is indisputable.…”
Section: Discussionmentioning
confidence: 99%
“…This work is timely and important to inform public health and clinical climate change vulnerability assessments and disaster planning (48). Our work is also crucial to developing climate change equity interventions focused on health and education(49), such as enhancing precision in the direct provision of disaster preparedness supplies or household disaster planning services to those identified as most at-risk or affected.…”
Section: Discussionmentioning
confidence: 99%
“…Building enduring public and political will for climate and health solutions may therefore be the most important-and promising-public health objective for the next several decades. Health professionals have long intuited that acknowledging and promoting the human health benefits of climate solutions as "co-benefits" of climate action would help advance this objective (16)(17)(18)(19). Social science research conducted over the past decade has confirmed this intuition and refined it.…”
Section: Climate Solutions Are Health Solutionsmentioning
confidence: 99%
“…Many of the actions in each of these categories also produce health benefits and, if done right, equity benefits ( 15 ). Therefore, climate solutions have “co-benefits” that can quickly improve public health and wellbeing while also helping to stabilize the climate ( 16 19 ). Table 1 provides examples of the types of climate solutions and adaptation measures and their associated climate and health benefits.…”
Section: Climate Solutions Are Health Solutionsmentioning
confidence: 99%
See 1 more Smart Citation